2022
DOI: 10.1016/j.dib.2021.107715
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic dataset of the moss Physcomitrium patens PSEP3 KO and OE mutant lines

Abstract: Small open reading frames (<100 codons) that are located on long noncoding RNAs (lncRNAs) can encode functional microproteins. These microproteins are shown to play important roles in different cellular processes, such as cell proliferation, development and disease response [1] , [2] , [3] , [4] , [5] , [6] . However, there are only a few known lncRNA-encoded functional micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Overexpression and knockdown studies of these lncRNA-encoded peptides have revealed morphological variations showing their role in moss growth and development: (i) knocking out a 40-aa peptide encoded by lncRNA Pp3c18_sORF57 showed a slight decrease in moss plant diameter on medium with glucose and without ammonium tartrate. Moreover, no changes have been observed in protonemal architecture and the number of leafy shoots or filament branching in knockouts; (ii) overexpression of a 41-aa peptide encoded by the Pp3c9_sORF1544 results in longer filaments implicated in a rapid radial extension of the protonemal tissues compared to the wild-type lines; (iii) knocking out a 61-aa peptide encoded by conserved Pp3c25_sORF1000 results in a decrease in growth rate and altered protonemal architecture on medium without glucose but supplemented with ammonium tartrate; (iv) the lines with a knockout in a 57-aa peptide encoded by an additional conservative lncRNA Pp3c25_sORF1253 display a decrease in protonemata growth rate and altered filament branching [ 40 , 42 ].…”
Section: Possible Effects Of Lncrna-encoded Peptides On Plant Physiol...mentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression and knockdown studies of these lncRNA-encoded peptides have revealed morphological variations showing their role in moss growth and development: (i) knocking out a 40-aa peptide encoded by lncRNA Pp3c18_sORF57 showed a slight decrease in moss plant diameter on medium with glucose and without ammonium tartrate. Moreover, no changes have been observed in protonemal architecture and the number of leafy shoots or filament branching in knockouts; (ii) overexpression of a 41-aa peptide encoded by the Pp3c9_sORF1544 results in longer filaments implicated in a rapid radial extension of the protonemal tissues compared to the wild-type lines; (iii) knocking out a 61-aa peptide encoded by conserved Pp3c25_sORF1000 results in a decrease in growth rate and altered protonemal architecture on medium without glucose but supplemented with ammonium tartrate; (iv) the lines with a knockout in a 57-aa peptide encoded by an additional conservative lncRNA Pp3c25_sORF1253 display a decrease in protonemata growth rate and altered filament branching [ 40 , 42 ].…”
Section: Possible Effects Of Lncrna-encoded Peptides On Plant Physiol...mentioning
confidence: 99%
“…Particularly, the CRISPR-cas9-mediated gene editing approach can be applied to check the potential activities of peptides. Alternatively, in planta overexpression of small peptides or expression driven by a native promoter, there may also be useful ways to study the lncRNA-encoded peptide functions via genetic approaches [ 17 , 24 , 40 , 41 , 42 ]. On the other hand, the use of artificially produced lncRNA-encoded peptides with a high purity and/or desired labeling provides an effective tool for studying plant small peptide functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that a small proportion of the identified lncRNAs are potential pseudogenes. Overexpression and knockout of P.patens lncORFs Pp3c9_sORF1554, Pp3c25_sORF1253, Pp3c25_sORF1000, and Pp3c18_ resulted in morphological changes ( Mamaeva et al., 2022 ).…”
Section: Small Open Reading Frame Encoded Peptidesmentioning
confidence: 99%
“…Making use of this genetic resource, several proteomic datasets were acquired in the last two decades giving insights into abiotic stress and desiccation tolerance‐associated proteins in protonema and gametophores (Cho et al., 2006; Cui et al., 2012; Luo et al., 2020; Mamaeva et al., 2022; Sarnighausen et al., 2004; Skripnikov et al., 2009; Toshima et al., 2014; Wang et al., 2010; Wang, Yang, Zhang, et al., 2009; Wang, Yang, Liu, et al., 2009; Wang et al., 2008; Yotsui et al., 2016).…”
Section: Introductionmentioning
confidence: 99%